Sürekli periton diyalizi ilişkili peritonit: Kocuria kristinae. Olgu sunumu ve literatür derlemesi - (:unkn) unknown (My University, 2017)
Kocuria kristinae, Micrococcaceae ailesinden gram pozitif kok şeklinde bir bakteridir Kocuria kristinae deride, mukoza ve orofarinkste kolonize olur. İmmünosüprese hastalarda oportünist bir patojen olarak infeksiyonlara neden olabilir.Bu yazıda sürekli ayaktan periton diyalizi (SAPD) tedavisi gören bir hastada Kocuria kristinae'ye bağlı gelişen akut peritonit olgusu sunulmuştur. Diğer SAPD tedavisi gören hastalardaki Kocuria kristinae peritonitleri gözden geçirilmiştir.SAPD tedavisi gören hastalarda Kocuria kristinae patojen olarak bildirildiğinde bu mikroorganizmanın klinik önemi küçümsenmemelidir.

Kocuria kristinae is a gram-positive coccus of Micrococcaceae family. Kocuria kristinae inhabits the skin and mucous membranes. It can cause opportunistic infections in patients with indwelling devices and severe underlying diseases.We describe here a case of acute peritonitis caused by Kocuria kristinae in a patient on continuous ambulatory peritoneal dialysis (CAPD). Additionally, a review of other reported CAPD related peritonitis by Kocuria kristinae is provided.The importance of Kocuria kristinae as a pathogen in patients with CAPD peritonitis should not be underestimated.
Uncommon presentation of CAPD-related peritonitis with unusual organism: Kocuria kristinae. Case report and review of the literature
Keywords: Genel ve Dahili Tıp